NOVEL SYNTHESIS, CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY OF SILVER NANOPARTICLES USING LEAF EXTRACT OF MELOTHRIA MADERASPATANA (LINN) CONG - Srinivasan, Subramani; Indumathi, Dhananjayan; Sujatha, Mathiyazhagan; Sujithra, Kathiroli; Muruganathan, Udaiyar (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: This study aims to investigate the green synthesis of silver nanoparticles (AgNPs) Melothria maderaspatana (MM), and evaluation of their antibacterial activities for the first time. It is observed that MM leaf extract can reduce silver ions into AgNPs. Methods: The obtained particles were analyzed by UV-visible spectrophotometry, scanning electron microscopy (SEM), Fourier transform infrared (FT-IR) spectroscopy, to understand the morphology of AgNPs. In addition, the antibacterial activity by MM extract synthesized AgNPs (MM AgNPs) was also investigated. FTIR spectroscopic studies were carried out to find possible bio-reducing agent present in the plant leaves. Results: The formation and stability of the reduced AgNPs in the colloidal solution were monitored by UV-Vis spectrophotometer analysis.SEM and FT-IR spectra of the leaf extract after the development of nanoparticles are determined to allow identification of possible functional groups responsible for the conversion of metal ions to metal nanoparticles. Conclusion: Further, the AgNPs thus acquired showed highly potent antibacterial activity toward Gram-positive (Bacillus cereus) and Gram-negative (E. coli, pseudomonas aeruginosa, and Klebsiella sps) microorganisms. Keywords: Green synthesis, Nanoparticles, Melothria maderaspatana, Antibacterial activity, Human pathogens